IMPROVING STUDENTS VOCABULARY BY USING SONGS AND GAME - ; Wijaya, Bambang; ., Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: Improving Students Vocabulary by Using Songs and Games is a Classroom Action Research at Second Grade Students of SD Kristen Kanaan Sungai Raya Dalam in Academic Year 2011 / 2012. The aim of this research is to know how the use of songs and game improve the students vocabulary achievement. The researcher used classroom action research as the method of this research. Based on the analysis of the students test result, the writer describes the qualification of students mean score in third cycles (90.0) which reached 100% of achievement score is Excellent. Key Word: vocabulary, using songs, game. Abstrak: Meningkatkan penguasaan kosa kata anak dengan menggunakan lagu dan permainan merupakan sebuah Penelitian Tindakan Kelas pada siswa kelas dua di SD Kristen Kanaan Sungai Raya Dalam Tahun Ajaran 2011 / 2012. Penelitian ini bertujuan untuk mengetahui bagaimana lagu dan permainan meningkatkan penguasaan kosa kata anak. Peneliti pnaggunakan penelitian tindakan kelas sebagai metode dalam penelitian ini. Berdasarkan analisa hasil tes siswa, penulis menyimpulkan bahwa kualifikasi nilai rata-rata siswa apda putaran ketiga (90,0) yang mana mencapai nilaiketuntasan 100% dikategorikan Excellent. Kata Kunci: kosa kata, penggunaan lagu, permainan